2009
DOI: 10.2989/ajar.2009.8.3.8.929
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between HIV and alcohol use in a remote Namibian mining community

Abstract: In southern Africa, the use of alcohol is increasingly seen as creating a context of risk for HIV transmission. This qualitative study investigates the links between alcohol use and higher-risk sexual behaviours in a remote southern Namibian mining-town community. Using data from six focus groups and 16 in-depth interviews conducted in 2008, the researchers investigated knowledge of the link between alcohol consumption and HIV risk, focusing on the specific mechanisms related to drinking and higher-risk sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…20 1 (Erinosho et al, 2012) -Gendered patterns of substance use Studies reported that experiences with drug and alcohol use for women-centered more on the personal and emotional aspects of drug-related experiences while men's experiences focused more on external factors such as socialisation and financial gain from sale of drugs. For example, in the mining sector, men employed in lower-ranking jobs often drank together in groups without interference from their family members whom they were often separated from, and to foster their group identity (Lightfoot, Maree, & Ananias, 2009). Similarly, in fishing communities, fishermen collectively used drugs and alcohol to cope with work-related stress (Sileo et al, 2016).…”
Section: --mentioning
confidence: 99%
“…20 1 (Erinosho et al, 2012) -Gendered patterns of substance use Studies reported that experiences with drug and alcohol use for women-centered more on the personal and emotional aspects of drug-related experiences while men's experiences focused more on external factors such as socialisation and financial gain from sale of drugs. For example, in the mining sector, men employed in lower-ranking jobs often drank together in groups without interference from their family members whom they were often separated from, and to foster their group identity (Lightfoot, Maree, & Ananias, 2009). Similarly, in fishing communities, fishermen collectively used drugs and alcohol to cope with work-related stress (Sileo et al, 2016).…”
Section: --mentioning
confidence: 99%
“…, Lightfoot et al . ). As a consequence, the prevalence of HIV and STIs has often been found to be higher in the mining sector than in the general population (Seguy et al .…”
Section: Introductionmentioning
confidence: 97%
“…Paying for sex and having multiple partners are common among men in mining communities (Desmond et al 2005). Sexually transmitted infection and HIV risk factors for men in mining areas are well documented and include never using condoms with female sex workers or partners and drug and alcohol use (Xu et al 2008, Lightfoot et al 2009). As a consequence, the prevalence of HIV and STIs has often been found to be higher in the mining sector than in the general population (Seguy et al 2008, Zhang et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies examined this link in other African countries (Desmond et al 2005; Kis 2007; Lightfoot, Maree & Ananias 2009), and outside of Africa there have been a further three studies (Faas, Rodriguez-Acosta & Echeverria de Perez 1999; Linhares & Mello 1989; Zhang et al 2007). However, literature searches did not reveal any study which linked those two issues (mining and HIV) together with measures of the quality of life of miners or members of their communities.…”
Section: Literature Reviewmentioning
confidence: 99%